Environmental Pollution and its Prevention: A Critical Analysis in the light of Sīrah Studies - Karim Dad; Jadoon, Saeed-ul-Ḥaq; Khan, Abzahir (Journal of Islamic and Religious Studies, 2019)
Today, the whole world is facing the dangerious issues of environmental pollution. There is a lot of piles of garbage, plastic bags and waste are found in common routes and streets, the use of bacterial and antiseptic chemicals, smoking as well as the excessives use of machinery causes the abundance of smoke and due to the noise of vehicles, rugs, motorcycles, factories and airplanes, our daily pollution is increasing daily. As a result, many problems including various types of illness and seasonal variations are becoming a major challenge for today's modern era. In order to deal with it, it is important for us to study and follow the instructions of the Prophet (PBUH). Prophet (PBUH) has taken important measures to protect environmental pollution. He has prescribed some precautionary measures to prevent the spreading of dirt in society and keeping the environment clean to avert the soil pollution. For the purpose of aviation of air pollution, the prophet has ordered to populate it with the livestock andplantation. To cope with water pollution, it was emphasized to keep water clean and cleaness of air from odor and dirt. In this modern era, prevention of environmental pollution without following these instructions is impossible. This article has invesitaged on prevention of enviromental pollution and cleanliness of enviroment in the light of Sīrah.